2017
DOI: 10.1371/journal.pone.0189734
|View full text |Cite
|
Sign up to set email alerts
|

Intensity matters: Therapist-dependent dose of spinal transcutaneous electrical nerve stimulation

Abstract: The intensity used during transcutaneous electrical nerve stimulation (TENS) in both, clinical practice and research studies, is often based on subjective commands such as “strong but comfortable sensation”. There is no consensus regarding the effectiveness dose of TENS. The objective was to determine the difference in the effect of spinal TENS on soleus H-reflex modulation when applied by two therapists instructed to apply the stimulation at a “strong but comfortable” intensity. Twenty healthy volunteers divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Rather than setting the stimulation intensity objectively, most of the studies that met the inclusion criteria for review instead expressed it using subjective and ambiguous terms of perception of the current by participants or observations by researchers. Recently, Serrano et al 43 showed that, when therapists set the intensity of the current on the basis of subjective terms of perception of the stimulus, the defined stimulus intensity is highly variable, which in turn has an impact on the therapeutic effect. Despite the lack of sufficient data to perform a correlational analysis between the stimulus intensity and motor effect, computational models 17,42 indicate that the intensity needed to depolarize the dorsal root afferent fibers, at the dorsal root entry zone, should be ≥17.6 V because it is estimated that the amount of current that penetrates this region through the intervertebral tissues is only 9%.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than setting the stimulation intensity objectively, most of the studies that met the inclusion criteria for review instead expressed it using subjective and ambiguous terms of perception of the current by participants or observations by researchers. Recently, Serrano et al 43 showed that, when therapists set the intensity of the current on the basis of subjective terms of perception of the stimulus, the defined stimulus intensity is highly variable, which in turn has an impact on the therapeutic effect. Despite the lack of sufficient data to perform a correlational analysis between the stimulus intensity and motor effect, computational models 17,42 indicate that the intensity needed to depolarize the dorsal root afferent fibers, at the dorsal root entry zone, should be ≥17.6 V because it is estimated that the amount of current that penetrates this region through the intervertebral tissues is only 9%.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity was gradually increased until a minimally visible contraction was observed and subsequently decreased until it disappeared, and this sensation remained throughout the session. To avoid habituation to the stimulus, participant were asked every 2 minutes to corroborate the perceived sensation, and the intensity was increased if requested [ 6 , 7 ]. The same procedure was performed with the 5 kHz stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…The intensity was gradually increased until a minimal visible contraction was observed and then subsequently decreased until the muscle contraction disappeared, with the same intensity maintained throughout the stimulation. To avoid habituation to the stimulus, participants were asked to corroborate the perceived stimulation sensation every 2 min, so that the stimulation intensity could be increased if requested [21,22].…”
Section: Khz Stimulationmentioning
confidence: 99%